BUDDHA -INVOCATION AS KOAN (NIEN-FO) - Chung-fang Yu (Journal of Dharma, 2020)
Pure Land and Ch’an have been the two most influential schools of Chinese Buddhism since the T’ang (618-907 A.D.). When people think of these two traditions, they usually like to stress their differences. In fact, there are certain neat contrasts between them. For instance, while Pure Land Buddhism stresses the saving power of Amitabha’s original vow, Ch’an tells its practitioner to discover his true nature through his own effort. While Pure Land extols the beatitude of the land of Sukhavati, Ch’an is relentless in its denial of all dualities. While Pure Land recognizes the sufficiency of the simple and believing heart, Ch’an recognizes nothing short of the radical transformation brought about by one’s experience of awakening. The Pure Land practitioner is deeply aware of his inherent human weaknesses and hopes to overcome them through egoless devotion to the Buddha. The Ch’an practitioner, however, hopes to transcend the human condition by re-enacting in his own life the enlightenment of the Buddha. In a sense, Pure Land is indeed the religion of "Other Power" and Ch’an, the religion of "Self Power".